Comparative Study Of Pneumonia Severity Index (Psi) & Curb-65 Score In Assessing Severity Of Community Acquired Pneumonia (Indian Journal of Applied-Basic Medical Sciences, 2021)
INTRODUCTION: Community acquired pneumonia (CAP) is a common disorder with an incidence of about 20% to 30% in  developing countries compared to an incidence of 3% to 4 % in developed countries. It is very difficult to find  causative organism of community acquired pneumonia in every patient despite aggressive laboratory  investigation and blood or sputum culture and it takes few days for it. It is believed that definite prognostic score  will be very useful for stratifying patients at high risk and require critical care unit treatment. Pneumonia severity  index (PSI) score and CURB-65 Score are two prognostic scoring systems that can stratify patients requiring  intensive care unit treatment. Each prognostic score has individual pros and cons and both can be used  supplementary to each other. So here we want to study the reliability and validity of PSI and CURB 65 score in  Indian population with pneumonia. MATERIAL & METHOD: A hospital based comparative observational study included total 50 patients with pneumonia based on inclusion  and exclusion criteria. Complete clinical history and physical examination done. At the time of initial evaluation,  chest radiograph was done and repeated after 48 hours. ECG, ABGA, serum electrolyte measurement, sputum  for gram staining and culture, blood cultures (in selected patients), complete blood counts, blood urea nitrogen  and serum creatinine and fasting blood glucose were measured in every patient. Analysis was done with help of  SPSS software and using Microsoft Excel 2012. RESULTS: In our study, total 50 patients were enrolled among them 34 patients were male while 16 patients were female.  Most common organism cultured was klebsiella species that was in 18 (36%) patients while 18 patients had no  organisms seen in sputum culture. In our study, 8(16%) patients were died out of 50 patients admitted. PSI class  4 showed highest sensitivity in predicting mortality 50%, while specificity was highest for class 2 with 90.4%,  followed by class 5 with 73.8%. The PPV was highest for class 4 22%, and NPV was highest for class 4 87.5%.  Among CURB 65 score, class 4 showed highest sensitivity in predicting mortality 50%, while specificity was  highest for class 4 with 92.8%, followed by class 3 with 85.7%. The PPV was highest for class 4= 57.1%, and  NPV was highest for class 4= 90.6%. CONCLUSION: It is observed that PSI has better specificity and negative predictive value (NPV) but less sensitivity and positive predictive value (PPV). This is because impact of age is observed in PSI which leads to lower estimation of  severity of CAP mostly in young patients who have no other comorbidities. The two scoring CURB-65 and PSI  approaches have to be viewed at the most as being complementary as each has different strengths and weaknesses.  With help of CURB-65 and PSI Score, we can better understand the prognosis and classify patients on basis of  severity and adequate utilization of resources and proper treatment to improve outcome in developing countries  like India.
Keywords: Community Acquired Pneumonia (CAP); Pneumonia Severity Index (PSI); CURB-65